2017
DOI: 10.1186/s13287-017-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

Pellet coculture of osteoarthritic chondrocytes and infrapatellar fat pad-derived mesenchymal stem cells with chitosan/hyaluronic acid nanoparticles promotes chondrogenic differentiation

Abstract: BackgroundCell source plays a key role in cell-based cartilage repair and regeneration. Recent efforts in cell coculture have attempted to combine the advantages and negate the drawbacks of the constituent cell types. The aim of this study was to evaluate the chondrogenic outcome of articular chondrocytes (ACs) and infrapatellar fat pad (IPFP)-derived mesenchymal stem cells (MSCs) in direct coculture.MethodsACs and IPFP MSCs from the same patients with knee osteoarthritis (OA) were cocultured in monolayer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 46 publications
0
35
0
1
Order By: Relevance
“…CS derivative carboxymethyl-CS in a dose-dependent manner reduced the inflammatory profile of primary rat chondrocytes by reducing iNOS expression and upregulating the anti-inflammatory cytokine IL-10 in vitro [87]. In another study, the addition of hyaluronic acid-CS NPs to a pellet co-culture of the human infrapatellar fat pad (IPFP)-derived mesenchymal stem cells (MSCs) with osteoarthritic chondrocytes increased chondrogenic differentiation [88]. Human IPFP-MSCs seeded on 3D-printed CS scaffolds in chondrogenic media containing TGF-β3 and BMP-6 attach, proliferate, and differentiate into chondrocyte-like cells modulating the formation of cartilaginous tissue in vitro [89].…”
Section: Cartilagementioning
confidence: 98%
“…CS derivative carboxymethyl-CS in a dose-dependent manner reduced the inflammatory profile of primary rat chondrocytes by reducing iNOS expression and upregulating the anti-inflammatory cytokine IL-10 in vitro [87]. In another study, the addition of hyaluronic acid-CS NPs to a pellet co-culture of the human infrapatellar fat pad (IPFP)-derived mesenchymal stem cells (MSCs) with osteoarthritic chondrocytes increased chondrogenic differentiation [88]. Human IPFP-MSCs seeded on 3D-printed CS scaffolds in chondrogenic media containing TGF-β3 and BMP-6 attach, proliferate, and differentiate into chondrocyte-like cells modulating the formation of cartilaginous tissue in vitro [89].…”
Section: Cartilagementioning
confidence: 98%
“…Obese mice have stronger IPFP-ASC adipogenic differentiation potential than thin mice [67]. Hyaluronic acid also can enhance adipogenic differentiation [52]. Lopa et al [84] have reported that IPFP-ASC adipogenic differentiation potential is similar between young people and old people.…”
Section: Adipogenic Differentiationmentioning
confidence: 99%
“…Inducing ASCs after inhibiting ET receptor Promoting adipogenic differentiation [50] 2018 Human Sc-ASCs AtECM Promoting adipogenic differentiation in the first 7 days of differentiation induction [70] 2017 Human IPFP-ASCs Hyaluronic acid Promoting adipogenic differentiation [52] 2017 Human IPFP-ASCs RHEB overexpression in IPFP-ASCs Promoting adipogenic differentiation [56] 2017 Human Sc-ASCs Addition of 2, 5, and 10 μm of pyrintegin Lipid accumulation is the most marked in 2 μm of pyrintegin [85] 2016 Human Sc-ASCs miRNA-29b overexpression in Sc-ASCs Promoting adipogenic differentiation [86] 2016 Human ASCs from Life Technology (USA)…”
Section: Adipogenic Differentiationmentioning
confidence: 99%
“…Cartilage samples were obtained intraoperatively from patients (n = 3, age 55 ± 10) undergoing total knee arthroplasties with approval from Ethics Committee of Southwest Hospital (Chongqing, China). Chondrocytes were isolated according to our previous protocol [19]. Briefly, cartilage pieces were digested in high-glucose DMEM (C11995500BT, Gibco, USA) supplemented with 0.2% type II collagenase (C6885, Sigma, USA) and 1% penicillin/streptomycin (P/S) overnight at 37 °C.…”
Section: Cell Isolation and Culturementioning
confidence: 99%